Designing An Innovation Model For Ips Learning - Ade Isma Nurfata; Asgipen Debataraja; Mugniar Handayani; Candri Ratna Palupi; Yayan Sudrajat (Journal of Instructional Development, Innovation, and Evaluation, 2023)
It is anticipated that the low level of learning will tend to decrease if faced with very rapid changes in society. This relates to the very rapid use of science and technology in various aspects. Strategy based on paradigm, that there are two forces that influence the demands and challenges of education. First, education is faced with the challenge of playing a role in strengthening the value system, in enhancing the quality of faith and devotion. Second, education is faced with paradigmatic demands to play education in mastering science and technology. This challenge arises and demands to be faced simultaneously, and demands a strategic answer by integrating policy and culture within the framework of improving the quality of Indonesian people to welcome 2020 through improving the quality of education. This challenge, which is related to innovation in the learning process, clearly demands a conceptual direction regarding innovation in the learning process, so that students have the ability to empower the potential of faith and devotion to God Almighty as a spiritual force and how learning can effectively empower potential in mastering science and technology. In essence, social studies learning innovation is an effort to continuously improve the quality of the educational process, to meet the development of society's demands for education. In this way, innovation in social studies learning will be effective, when indicated by the results of evaluation and research in the field of social studies learning. Learning can be done in joint study groups, which emphasizes group learning. So far, it has been felt that it has not been deliberately developed in the learning process, therefore it is a challenge and demand for learning innovation. If done, it will be able to overcome the weaknesses of learning that has been carried out in the fiel. Keywords: Innovation, Learning, Social Sciences